2017
DOI: 10.1007/s12094-017-1709-z
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant versus salvage radiotherapy in prostate cancer: multi-institutional retrospective analysis of the Spanish RECAP database

Abstract: This is the first nationwide study in Spain to evaluate a large cohort of PCa patients treated with RP followed by postoperative RT. ART yielded better 2- and 5-year BRFS rates, although OS was equivalent. These findings are consistent with most other published studies and support ART in patients with adverse prognostic characteristics after radical prostatectomy. Prospective trials are needed to compare immediate ART to early SRT to better determine their relative benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…A retrospective cohort study demonstrated that adjuvant RT, compared with salvage RT, was associated with reduced biochemical recurrence, distant metastasis, and mortality for patients with adverse pathology . Similar findings were presented in a Spanish nationwide cohort study, in which adjuvant RT yielded better 2‐ and 5‐year biochemical relapse‐free survival outcomes but equivalent OS rates compared with salvage RT .…”
Section: Resultssupporting
confidence: 61%
“…A retrospective cohort study demonstrated that adjuvant RT, compared with salvage RT, was associated with reduced biochemical recurrence, distant metastasis, and mortality for patients with adverse pathology . Similar findings were presented in a Spanish nationwide cohort study, in which adjuvant RT yielded better 2‐ and 5‐year biochemical relapse‐free survival outcomes but equivalent OS rates compared with salvage RT .…”
Section: Resultssupporting
confidence: 61%
“…Seven studies took RP as the starting point of follow-up and reported corresponding results [1418, 21, 22]. Six studies followed RT as the basis of follow-up and reported related results [19, 20, 23, 24, 27, 28]. The remaining two studies reported respectively results at different follow-up starting points [25, 26].…”
Section: Resultsmentioning
confidence: 99%